The problem of “complicated wounds” and complicated wound process in female patients with breast cancer and approaches to its solution - A. A. Supilnikov; L. A. Trusova; E. V. Batukhtina; A. E. Makhlin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The review of the literature is devoted to the methods of complicated wounds treatment in patients with breast cancer. The main reasons of non-healing wounds after the radical mastectomy are studied; the general principles of chronic wounds treatment and the main ways of solving this problem are also studied.